Toward urban-rural linkage development: contribution of climate-adaptive agroecology in the lower Chao Phraya River Basin, Thailand - Hongsprabhas, Parichat (Frontiers in Sustainable Cities, 2023)
This case study proposed a hypothesis on initiating urban-rural co-development using food as a medium to drive the transformation of the food systems and sustainable consumption. I applied the guiding principles of the United Nations Habitat to the water-retention areas under the nature-based solution for flood mitigation in the central region, the main rice-growing area of Thailand. I reviewed the partnerships of primary institutions, namely public, private, and universities, supporting and intertwining with civil society through Thai cultural and social norms after the 1997 economic crisis. The critical aspects included the sufficiency economy philosophy at the household level as a foundation of national policies. Recent policies and measures on food and nutrition security, alternative farming practices, and incentives to increase sustainable agroecology were prioritized post-COVID-19. This research suggests additional measures enabling agroecology and landscape improvement in rural areas connecting the cities of Ayutthaya and Bangkok to enhance market access for small producers and consumers in rural and urban areas with limited resources. A better community-based adaptation, ecological outcomes, and sustainable social inclusion in flood-prone lowlands could support the food sovereignty and capacity-building of Thailand as one of the world's major food exporters under climate extremes.